Nigeria : economy and society - Williams, Gavin (London : Rex Collings, 1976)
It discusses the political economy of Nigeria.
Includes bibliographical reference and index.
occ 16/01/2019
Loans
Keywords: Politics and government; Social conditions; Economic history; Nigeria